Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Penumpang di Bandar Udara: Studi Literatur dari Perspektif Layanan, Teknologi, dan Operasional - Shabira Afina Pajri; Ubaedillah Ubaedillah (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to analyze the factors that affect passenger satisfaction at the airport through three main perspectives, namely: service, technology, and operations. The approach used is a literature study of ten scientific journals that discuss airport service quality from various aspects. The results of the study show that service quality, especially those covering SERVQUAL dimensions such as reliability, responsiveness, empathy, assurance, and physical evidence, plays a major role in shaping service user perceptions. The technology perspective, through the implementation of self-service such as self check-in, Flight Information Display Sistem (FIDS), and digital service applications, is proven to increase efficiency and convenience, even contributing up to 96.8% to user satisfaction according to one study. Meanwhile, from an operational perspective, aspects such as queue time at check-in counters, public facilities, and accessibility to the terminal also have a significant impact on the overall passenger experience. The conclusion of this study emphasizes the importance of integration between the three perspectives in designing strategies to improve airport service quality. Suggestions are given to airport managers to continue to improve services, expand technology adoption, and reorganize operations to create a safe, comfortable, and satisfying travel experience for all service users